Optimizing Access to Justice Through the Prodeo and Sidang Keliling in Boroko Religious Court - Mustafa, Irawati; Rajafi, Ahmad; Lahilote, Hasyim Sofyan; Pedju, Rizaldy Purnomo (IAIN Manado, 2024)
This study evaluates the effectiveness of implementing the Prodeo and Sidang Keliling at the Boroko Religious Court in PERMA No. 1 of 2014. The research method used is qualitative with a juridical-empirical approach, including data collection through in-depth interviews, observations, and document analysis. The results showed that implementing the two programs significantly increased access to justice for the underprivileged. However, fluctuations were found in the realization of annual cases, highlighting the need for budget adjustments and more effective socialization strategies. The discussion emphasized the importance of adapting legal services to the needs of local communities and integrating the provider approach into the broader justice system. The conclusion of this study suggests that with improved management and socialization, the Prodeo and Sidang keliling can continue to effectively support the principles of social justice and broader access to legal services. The implications of this study lead to policy recommendations to optimize resource allocation and socialization strategies in the Indonesian judicial system, especially in the Boroko Religious Court.